2017
DOI: 10.1016/j.exer.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology of lens development: A paradigm for disease gene discovery in the eye

Abstract: Over the past several decades, the biology of the developing lens has been investigated using molecular genetics-based approaches in various vertebrate model systems. These efforts, involving target gene knockouts or knockdowns, have led to major advances in our understanding of lens morphogenesis and the pathological basis of cataracts, as well as of other lens related eye defects. In particular, we now have a functional understanding of regulators such as Pax6, Six3, Sox2, Oct1 (Pou2f1), Meis1, Pnox1, Zeb2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 144 publications
1
38
0
1
Order By: Relevance
“…It has been shown that enriched expression in developing lens tissue can be used as a criterion to evaluate potential function in lens development (Lachke et al 2011, 2012a, b; Anand and Lachke 2016; Anand et al 2015; Agrawal et al 2015; Kasaikina et al 2011; Wolf et al 2013; Manthey et al 2014; Dash et al 2015; Audette et al 2016). Consistent with those data, we find that all six candidates are significantly expressed in mouse lens development, and five exhibit lens-enrichment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that enriched expression in developing lens tissue can be used as a criterion to evaluate potential function in lens development (Lachke et al 2011, 2012a, b; Anand and Lachke 2016; Anand et al 2015; Agrawal et al 2015; Kasaikina et al 2011; Wolf et al 2013; Manthey et al 2014; Dash et al 2015; Audette et al 2016). Consistent with those data, we find that all six candidates are significantly expressed in mouse lens development, and five exhibit lens-enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…To gain insights into the significance of each of the cataract-linked candidate genes in this study ( TAPT1 , RIC1 , CYP51A1 , GEMIN4 , TAF1A and WDR87 ) we applied our published approach of using lens expression analysis (Lachke et al 2012; Anand and Lachke 2016). Mouse orthologs of these genes were investigated for their expression and enrichment in mouse lens expression microarrays datasets using iSyTE database (Lachke et al 2012) and publicly available mouse lens microarray data.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we demonstrated that for tissue-specific microarray datasets, an approach termed “ in silico WB-subtraction”, involving comparative analysis of the tissue in question to a “reference” WB dataset, provides estimates of tissue-specific enrichment that can be applied for prioritization of candidate genes. For the lens, we showed that tissue-enrichment is an excellent predictor of significance to lens biology, which has led to the identification and/or characterization of several new cataract-associated genes (Lachke et al 2012b; Anand and Lachke 2017; Kakrana et al 2018). Here, we tested the hypothesis that in silico WB-subtraction can be extended to process lens RNA-seq data and prioritize candidates important to lens biology and cataract.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, probe-hybridization kinetics plays major role in gene expression quantification unlike the direct detection of transcripts using RNA-sequencing. Thus, microarrays do not necessarily inform on the full repertoire of the transcriptome in a given cell or tissue type (Anand and Lachke 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Mediante el bloqueo de la actividad del gen Wnt1, SIX3 es capaz de prevenir la expansión anormal de la parte posterior del cerebro en la zona del cerebro anterior. Durante el desarrollo de la retina, SIX3 ha demostrado tener una función clave en la activación de PAX6 para promover el desarrollo del cristalino 34,35 . Además, SIX3 desempeña un papel estratégico en la activación de SOX2 36 .…”
Section: Six3unclassified